Skin tent on a nomad settlement at Angmagssalik. : Skindtelt på en nomade boplads i Angmagssalik. - Petersen, Sofie (University of Southern California Digital Library (USC.DL), 2015)
Skin tent on a nomad settlement at Angmagssalik.